Animated stunting counseling for department of Health Pagar Alam City based on multimedia - Muslim, Buhori; Firdaus, Ahmad N. (Institut Teknologi Dirgantara Adisutjipto, 2020)
Stunting counseling carried out by the Pagar Alam City Health Office is still conventional, explaining directly by extension agents and power points so that people who take part in extension activities are easily bored, this study aims to design and build media for stunting prevention using animation at the Pagar Alam City Health Service based on multimedia using adobe. Flash Cs6 is able to attract interest and eliminate the feeling of boredom of extension participants, the development stage of this research uses the ADDIE method, the ADDIE model development design consists of five steps, namely analysis, design, development, implementation, evaluation. This animation was built and designed using adobe flash CS6 actionscript 2.0 to measure the validity level of the animation. This countermeasure is used, namely expert reviews of experts, or alpha tests obtained from the results to see the level of understanding and public interest before and after the use of stunting control animation. This animation is expected to be able to help the health office of Pagar Alam City in making stunting education more efficient. The final result of this research is an animation of stunting control to increase public knowledge and become an animated video for the assistant of Pagar Alam City Health Office.